An Analysis of Beta-Blocker Administration Pre-and Post-Traumatic Brain Injury with Subanalyses for Head Injury Severity and Myocardial Injury. Issue 12 (December 2016) - Edavettal, Mathew; Gross, Brian W.; Rittenhouse, Katelyn; Alzate, James; Rogers, Amelia; Estrella, Lisa; Miller, Jo Ann; Rogers, Frederick B.
A growing body of literature indicates that beta-blocker administration after traumatic brain injury (TBI) is cerebroprotective, limiting secondary injury; however, the effects of preinjury beta blocker status remain poorly understood. We sought to characterize the effects of pre- and post-injury beta-blocker administration on mortality with subanalyses accounting for head injury severity and myocardial injury. In a Level II trauma center, all admissions of patients ≥18 years with a head Abbreviated Injury Scale Score ≥2, Glasgow Coma Scale ≤13 from May 2011 to May 2013 were queried. Demographic, injury-specific, and outcome variables were analyzed using univariate analyses. Subsequent multivariate analyses were conducted to determine adjusted odds of mortality for beta-blocker usage controlling for age, Injury Severity Score, head Abbreviated Injury Scale, arrival Glasgow Coma Scale, ventilator use, and intensive care unit stay. A total of 214 trauma admissions met inclusion criteria: 112 patients had neither pre- nor postinjury beta-blocker usage, 46 patients had preinjury beta-blocker usage, and 94 patients had postinjury beta-blocker usage. Both unadjusted and adjusted odds ratios of preinjury beta-blocker were insignificant with respect to mortality. However, postinjury in-hospital administration of beta blockers was found to significantly in the decrease of mortality in both univariate ( P = 0.002) and multivariate analyses ( P = 0.001). Our data indicate that beta-blocker administration post-TBI in hospital reduces odds of mortality; however, preinjury beta-blocker usage does not. Additionally, myocardial injury is a useful indicator for beta-blocker administration post-TBI. Further research into which beta blockers confer the best benefits as well as the optimal period of beta-blocker administration post-TBI is recommended.